Atlantic Cod (Gadus morhua) benefits from the availability of seagrass (Zostera marina) nursery habitat - Richard J. Lilley; Richard K.F. Unsworth (Global Ecology and Conservation, 2014)
The Atlantic cod (Gadus morhua) is a species of significant economic and historic importance but infamous for its decline. Apart from overfishing, the causes of this decline and its subsequent lack of recovery remain largely unresolved. Indeed, the degree to which specific habitats are important for this species remains unquantified at the scale of North Atlantic. Here, the literature on the role of eelgrass meadows (Zostera marina) as valuable nursery habitat for the Atlantic cod is reviewed and synthesized. Evidence is presented on relative densities of Atlantic cod in shallow water environments and in eelgrass meadows in comparison to alternative habitats. In addition, evidence pertaining to the ’viability gains’ attributed to the use of eelgrass meadows as nursery habitat (growth and survival) by juvenile Atlantic cod is analyzed. Although juvenile Atlantic cod use of Z. marina is found to be facultative, when possible, available literatures indicates that they may select Z. marina as a nursery habitat where they are found in high density (average of at least 246 ha−1). From their use of Z. marina habitat the juvenile Atlantic cod receives viability benefits from it, improving their chances of reaching maturation. This paper provides strong evidence that eelgrass meadows are of significant importance to contributing to Atlantic cod stocks. Keywords: Zostera marina, Eelgrass, Gadus morhua, Fisheries, Juveniles, Nursery habitat